Information Immobility and Foreign Portfolio Investment - Andrade, Sandro C.; Chhaochharia, Vidhi (Review of Financial Studies, 2010)
We examine how residents of the United States allocate their stock portfolios internationally. We find that a large U.S. Foreign Direct Investment (FDI) position in a destination country in 1990 is associated with a relatively large stock portfolio position in that country in the 2001–2006 period. Moreover, a change in the U.S. FDI position from 1980 to 1990 helps predict the change in the U.S. Foreign Portfolio Investment position from 1994 to 2006. These results are rationalized by Van Nieuwerburgh and Veldkamp’s (2009) equilibrium model of learning and portfolio choice under an information processing constraint. FDI establishes marginal differences in the endowments of information about different countries, which later translate into differences in stock portfolio holdings. We control for cross-country differences in capital controls, proximity along different dimensions, corporate governance, and economic and capital market development. Our results also hold for the G6 countries collectively.